2022
DOI: 10.5501/wjv.v11.i6.411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 on children with autism

Abstract: The coronavirus disease 2019 (COVID-19) pandemic affects all countries and populations worldwide, significantly impacting people with autism with a high risk of morbidity and mortality due to COVID-19. Approximately 25% of children with autism have an asymptomatic or symptomatic immune deficiency or dysfunction. In addition, they frequently have various comorbid conditions that increase the severity of COVID-19. In addition, severe COVID-19 during pregnancy may increase the risk of autism in the offspring. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…In previous studies, a positive correlation was found between COVID-19 and risk of developing neurodevelopmental disorders, including schizophrenia and pervasive developmental disorders. 39 , 40 The higher use of services for depression aligns with the WHO report indicating a 25% increase in the global prevalence of anxiety and depression during the COVID-19 pandemic related to social isolation, loneliness, fear of contracting infection, loss of family members, and financial constraint. 41 …”
Section: Discussionmentioning
confidence: 55%
“…In previous studies, a positive correlation was found between COVID-19 and risk of developing neurodevelopmental disorders, including schizophrenia and pervasive developmental disorders. 39 , 40 The higher use of services for depression aligns with the WHO report indicating a 25% increase in the global prevalence of anxiety and depression during the COVID-19 pandemic related to social isolation, loneliness, fear of contracting infection, loss of family members, and financial constraint. 41 …”
Section: Discussionmentioning
confidence: 55%
“…Social distancing measures have led to a rise in challenging behavior among autistic children [1,7], potentially increasing the risk of injury. Injuries, in turn, may necessitate hospitalization, posing a heightened risk of virus exposure for autistic children who are more vulnerable due to frequently occurring co-occurring medical conditions [5,54,55]. Furthermore, adding to caregivers' worries about injuries and safety, specifically the preference to avoid the necessity of medical interventions during the pandemic may have been exacerbated by suboptimal past experiences with healthcare institutions which are traditionally ill-prepared to address their children's unique needs in previous medical crises [56].…”
Section: Discussionmentioning
confidence: 99%
“…The intricate interplay between viral infections and neurodevelopmental disorders, particularly Autism Spectrum Disorder(ASD), has emerged as a pivotal area of research in recent years (2). Numerous studies have suggested a connection between prenatal viral infections, including Rubella, Herpes Simplex, Herpes Zoster, Cytomegalovirus, and a heightened risk of ASD in children (11)(12)(13)(14)(15).…”
Section: Viral Infections Viral Encephalitis and Autism Spectrum Diso...mentioning
confidence: 99%
“…Commonly developing during early childhood, the etiology of ASD is believed to be multifactorial, involving a complex interplay of genetic, environmental, and neurobiological factors. ASD has long been a subject of scientific inquiry, with emerging research suggesting that viral infections and subsequent viral encephalitis play a significant role in its onset (2)(3)(4)(5)(6)(7). Furthermore, there is a growing body of evidence that supports an association between the resurgence of latent viral infections and recent immunization events (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%